Analisis Patologi Sosial dalam Novel Unfamiliar Twins Karya Kadek Pingetania dengan Menggunakan Sosiologi Sastra sebagai Bahan Ajar Apresiasi Sastra di Kelas XII - Husna Naima; Dindin M. Zaenal Muhyi; Frilia Shantika Regina (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This study aims to explain the social pathology contained in novels that contain various kinds of bullying carried out by characters. This study will focus on (1) the study of literary sociology in the novel Unfamiliar Twins by Kades Pingetania with social pantology (2) the relationship between the study of literary sociology in the novel Unfamiliar Twins by Kades Pingetania with social pathology (3) the use of the novel Unfamiliar Twins by Kades Pingetania as learning material for Indonesian literature in high school. This research is a qualitative research to see various social pathologies in the novel Unfamiliar Twins by Kades Pingetania by analyzing the novel. The results of this analysis will be related to the types of bullying found in the novel Unfamiliar Twins by Kades Pingetania, namely: 1) bullying, 2) sexual harassment, 3) juvenile delinquency, and 4) cyberbullying and to real life and can be used as a reference to be used as teaching material in class XII.